Number of File Usage on Dentinal Defect Incidence of WaveOne GOLD and Reciproc NiTi Instruments - Koray Yılmaz; Taha Özyürek; Gülşah Uslu (Cumhuriyet University, 2018)
AbstractObjectives:To compare the incidences of dentinal defects caused by Reciproc and WaveOne GOLD NiTi files during root canal preparation and to exam the effect of number of file usage on the incidence of dentinal defect. Materials and Methods:Two hundred seventy mandibular incisor teeth were randomly divided into 3 different groups as follows: negative control (no preparation performed) (n: 30), Reciproc (n: 120) and WaveOne GOLD (n: 120) groups. The specimens were sliced at 3, 6 and 9 mm from the apex. Microscopic pictures of the specimens were taken with the aid of light emitting diode and the dentinal defects were examined. Results:There was no statistically difference among the WaveOne GOLD, Reciproc and control groups in terms of dentinal defect formation. The number of dentinal defects occurred in apical region in Reciproc group following 4thuse was found to be statistically higher than 1st, 2nd, and 3rduse in WaveOne GOLD group (P< .05).Conclusion:All the NiTi files tested in present study were found to cause defect in root canal dentin but there were not significant difference among the WaveOne GOLD, Reciproc and control groups in term of total dentinal defect formation